Development of a hybrid technique of solvent extraction and freeze-thaw for oil recovery from petroleum sludge - Abdulqawi, M.; A., Ibrahim; Rahimah, Embong; Norasyikin, Ismail (Elsevier Ltd, 2023)
The petroleum industry produces around 60 million tons of petroleum sludge annually, posing a considerable danger of environmental contamination. Crude oil recycling or recovery is critical to addressing this issue. While solvent extraction is a cost-effective and efficient technology, its low efficiency and unpredictability make it inadequate for crude oil extraction. Combining this method with the freeze-thaw process may boost oil extraction efficiency. With a 4:1 solvent-to-sludge ratio and a 30-minute extraction time, this study produced the maximum oil recovery rate of 50.98 % using cyclohexane. These findings show that the hybrid cyclohexane approach can recover up to 60.98 % of crude oil.